The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2193/2008-545
|View full text |Cite
|
Sign up to set email alerts
|

Detection Dogs: An Effective Technique for Bush Dog Surveys

Abstract: Detailed ecological data on the bush dog (Speothos venaticus) have been lacking, since standard field techniques, such as camera traps, have had little success recording their presence. This study eliminates dependence on visitation rate and switches the focus to locating evidence (e.g., olfactory) associated with the species’ natural behavior and movement patterns. Over a 3‐month period, a detection dog located multiple (n = 11, 4 confirmed and 7 potential) bush dog areas in Upper Paraná Atlantic Forest of Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 43 publications
0
56
0
1
Order By: Relevance
“…Despite scattered reports from the local community during occasional interviews over the seven years that we have worked in the region, the camera trap record was the first confirmed evidence of local bush dog occurrence. The low detection rate in our survey, in part, could be consequence of the species' tendency to avoid walking along roads and tracks (LIMA; JORGE; DALPONTE, 2009), or actively avoiding trails of large predators (DEMATTEO et al, 2009 Our bush dog record in the Triângulo Mineiro region, West Minas Gerais, bridges a gap in the known species occurrence within its expected geographical distribution in the Brazilian territory (JORGE et al, 2013). Despite that current highly fragmented landscape, Triângulo Mineiro region was regarded being environmentally suitable for the bush dog occurrence (ICMBIO, 2015).…”
Section: Contentsmentioning
confidence: 83%
“…Despite scattered reports from the local community during occasional interviews over the seven years that we have worked in the region, the camera trap record was the first confirmed evidence of local bush dog occurrence. The low detection rate in our survey, in part, could be consequence of the species' tendency to avoid walking along roads and tracks (LIMA; JORGE; DALPONTE, 2009), or actively avoiding trails of large predators (DEMATTEO et al, 2009 Our bush dog record in the Triângulo Mineiro region, West Minas Gerais, bridges a gap in the known species occurrence within its expected geographical distribution in the Brazilian territory (JORGE et al, 2013). Despite that current highly fragmented landscape, Triângulo Mineiro region was regarded being environmentally suitable for the bush dog occurrence (ICMBIO, 2015).…”
Section: Contentsmentioning
confidence: 83%
“…Brook et al (29) successfully located Javan rhinoceros ( R. sondaicus ) dung using two professional CDDs, after just 3 weeks of handler training and dog acclimation to the new handler and new working environment. Another study, by Dematteo et al (18), demonstrated the efficacy of professionally trained CDDs to work with an unfamiliar handler. These dogs successfully located the presence of bush dogs ( Speothos venaticus ) after only 2 weeks of handler training.…”
Section: Social Characteristics Likely To Affect Conservation Detectimentioning
confidence: 99%
“…Conservation detection now encompasses an array of activities, including detection of live wildlife (5–8), carcass detection for birds and bats around wind turbines (912), and detection of scats, pathogens, and other biological materials (1316). Several reports indicate that, in many cases, CDDs are more efficient than several other survey methods in detecting the presence/absence, and relative abundance, of plants and wildlife (3, 10, 15, 17, 18). These animals therefore represent an exciting opportunity which could substantially benefit conservation groups worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Detector dogs have been used to search for various species of carnivores (Wasser et al 2004;Smith et al 2005;Gompper et al 2006;Reindl-Thompson et al 2006;Long et al 2007a;Dematteo et al 2009;Brown et al 2011) and rodents (Gsell et al 2010;Duggan et al 2011;Shapira et al 2011). Detection probabilities can vary widely between species (e.g.…”
Section: Future Researchmentioning
confidence: 99%